3D-model and 3D-modeling in industrial design (Pedagogy of Higher and Secondary Education, 2009)
In the article undertake the attempt to formulate the definition of 3D-model and process of 3D-modeling in industrial design, cons hit definitive aspects of this conception from the position of industrial designer and todays production process.
Keywords: design; industrial design; 3D-model; 3D-modeling; virtual projecting; industrial projecting junctional model, structural model; assembly